Zahra Ayubi. Gendered Morality: Classical Islamic Ethics of the Self, Family, and Society. New York: Columbia University Press, 2019. 344 s. ISBN: 978-023-1191-33-3 - Elif Nur Erkan Balcı (Ankara Üniversitesi İlahiyat Fakültesi Dergisi)
Zahra Ayubi'nin Gendered Morality: Classical Islamic Ethics of the Self, Family, and Society isimli eseri değerlendirilmiştir.